Neo-Weberianism as a model for Public Administration reform in Brazil? Possible empirical explorations and applications - Pazini Papi, Luciana; Ziolkowski Padilha, Pablo; Thompson dos Santos, Gislaine (Revista del CLAD Reforma y Democracia, 2025)
The article explores the concept of the Neoweberian State (NWS) as an alternative to New Public Management (NPM), which emerged in Europe since the 2000s in response to the inability of NPM to address complex crises such as the 2008 financial crash and the COVID-19 pandemic. NWS combines traditional Weberian principles, such as the state’s legitimacy to coordinate markets, with modernizing elements of NPM and New Public Governance (NPG), such as transparency and performance-oriented management. While the concept has been consolidated in other contexts, its adoption in Latin America, particularly in Brazil, is still in its early stages. A systematic literature review was conducted using platforms such as Research Rabbit and Google Scholar, selecting 24 articles about NWS and its application in the region. The approaches were analyzed based on the depth of treatment of the concept. The study concludes that NWS is promising for Public Administration reform in Brazil, but its implementation requires adaptation to local specifics and strengthening state capacities. The article suggests the need for more empirical research to explore the applicability of NWS in Latin America, particularly in Brazil, where the concept is still at an early stage of development.
Keywords: Neo-Weberianism; Public Administration; Latin America; Brazil